A Minicomputer Based S.D.I. and Online Search System for Life Sciences - Rajashekar, T. B. (Journal of Information and Knowledge, 1986)
A major objective of the National Centre For Science Information is to provide Current Awareness to the science faculty members in Indian Universities and other educational institutions. Life Sciences, comprising Botany, Zoology, Biochemistry and related areas like Bioengineering, Agricultural and Environmental Sciences etc., is one of the major science disciplines for which N.C.S.I. is offering S.D.I. services. The weekly update tapes issued by Biosciences Information Service (BIOSIS), U.S.A., is input to the system. The service consists of a batch S.D.I. and an online search facility, software for which has been implemented on a minicomputer system dedicated to information handling. The paper describes the features of the microcomputer, input data base, user base and the search system, particularly the online search facility. It also deals with the system implementation and performance aspects.